2006
DOI: 10.1051/forest:2006003
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient status and field performance of tree seedlings planted in Mediterranean degraded areas

Abstract: -In degraded Mediterranean woodlands, nutrients, in addition to water, may be the major factors controlling reforestation success. But information on nutritional status of planted seedlings is scarce. We aimed to evaluate the nutritional status and field performance of Pinus halepensis and Quercus ilex seedlings planted on two characteristic Mediterranean forest soils developed from marl and limestone. We used root growth response to localized N and P enrichment, and foliar analysis as indicators of nutrient l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 36 publications
2
41
0
3
Order By: Relevance
“…We found low rates of seedling survival, consistent with previous studies on Quercus establishment in Mediterranean environments (Rey Benayas et al 2005;Castro et al 2006;Valdecantos et al 2006;Del Campo et al 2010, Cuesta et al 2010a. As we anticipated (H3), most of this mortality was a consequence of seedling predation; all of unprotected seedlings in the seeding experiment and at least 50 % of the naturally established seedlings (which were not protected) were predated by the end of the first growing season.…”
supporting
confidence: 79%
“…We found low rates of seedling survival, consistent with previous studies on Quercus establishment in Mediterranean environments (Rey Benayas et al 2005;Castro et al 2006;Valdecantos et al 2006;Del Campo et al 2010, Cuesta et al 2010a. As we anticipated (H3), most of this mortality was a consequence of seedling predation; all of unprotected seedlings in the seeding experiment and at least 50 % of the naturally established seedlings (which were not protected) were predated by the end of the first growing season.…”
supporting
confidence: 79%
“…III). It has been confirmed that high CaCO 3 concentrations in the soil solution can affect the germination and growth of seedlings, because they interfere in P and K assimilation [29,43]. In this sense, further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Poor tree survival in oak plantations has been frequently linked to restricted access to soil nutrients and the poor quality of seedlings grown in forest nurseries (Retana et al 1999;Tsakaldimi et al 2005;Valdecantos et al 2006). Although root pruning is known to impact shoot growth under in vitro conditions (Harmer and Walder 1994), the effects of nursery management practices on root plasticity remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%